Korean speaking and writing online learning during the COVID-19 pandemic: challenges and student perspectives - Shofura Agisda Fatunnisa (Journal of Korean Applied Linguistics, 2023)
Various challenges arose since the learning process in universities was carried out online due to the COVID-19 pandemic that hit the whole world. In order to have speaking and writing skills which are included as productive skills in language, students should do a lot of activities in the classroom directly by interacting a lot with both lecturers and other students. Korean Speaking and Writing course which must be carried out online without much time for preparation beforehand causes lecturers and students to experience difficulties at the beginning of online lectures. Therefore, this research was conducted to find out how Korean Speaking and Writing learning is carried out online, how students' perspectives on online learning take place, and what challenges students face when studying Korean Speaking and Writing online. This research is a qualitative descriptive study conducted at the Korean Language Education Study Program, Universitas Pendidikan Indonesia, focusing on second-year students. Through this research, it can be seen that: 1) Lecturers are quite good at teaching online by holding classes asynchronously using Google Classroom and synchronously with the Zoom application; 2) Students are of the view that online learning has its own advantages and disadvantages; 3) The challenges that arise from online Korean Speaking and Writing learning are the lack of self-motivation to study independently, external challenges in the form of a bad internet network, and difficulties in producing texts that are in accordance with Korean language rules.